O1-S06.02 Impact of pill sharing on drug-resistance and population-level effectiveness of a wide-scale oral PrEP intervention in resource-constrained settings. (10th July 2011) - Dimitrov, D; Boily, M C; Mâsse, B
Abstract : Background: In 2010 two randomised trials suggested that pre-exposure prophylaxis (PrEP) products based on tenofovir, an antiretroviral drug either administered daily orally (oral PrEP) or applied topically (vaginal microbicides), significantly reduced HIV acquisition among adherent users. Behavioural studies also suggest that some PrEP users are compelled to share product with sex partners, family, or friends. Pill sharing (PS) decreases the adherence levels of the intended PrEP users and creates an uncontrolled environment for the development of drug-resistance. However PS effects on the expected population-level impact of PrEP interventions have never been assessed. Thus, we aim to evaluate the potential impact of PS on the PrEP effectiveness to prevent HIV transmission and the spread of drug-resistance in heterosexual populations in resource-constrained settings. Methods: A transmission dynamic model was used to assess the population-level impact of oral PrEP in a variety of intervention scenarios and high HIV prevalence settings. The cumulative fractions of new HIV infections prevented (CPF) and transmitted drug-resistance (TDR) are evaluated over fixed time periods under various epidemiological conditions. The influence of different factors (eg, acquisition rate, PrEP coverage, rates of resistance development) on CPF and TDR is studied through simulations, using parameter sets sampled from ranges representative of countries in Sub-Saharan Africa. Results: Without PS, a 70% effective oral PrEP intervention used by 60% of the population prevents about 52% (95% CI 49.6% to 53.8%) of all new HIV infections over 10 years (10 years CPF) if adherence is 100%. CPF increases by 7% in populations with 10% PS, assuming no efficacy reduction for those who share PrEP and reduces by 2% if the efficacy reduction for sharers (prescribers or untracked users) is 50%. However, the fraction of transmitted drug-resistance (TDR) increases 2- to 6-fold in all scenarios investigated. It depends on the success in preventing PrEP usage by HIV infected individuals. Conclusions: PS may increase the PrEP coverage level achieved in the population but it also affects the PrEP efficacy for the users who do not follow the prescribed dosing. It creates a pool of untracked users who do not receive counselling, remain hidden and unreached by the effort to avoid the PrEP usage by HIV infected individuals. This increases substantially the potential risk of drug-resistance development.